The role of national culture on email usage among non-academic staff in Malaysian public universities - Bali Mahomed, Anuar Shah; Mcgrath, Michael G.; Bong, Zhi Yuh (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The Malaysian government has made extensive investment in the expansion of ICT and email usage in workplaces, particularly in the Higher Education Institutions. However, the levels of ICT as well as email usage have still not reached its optimum level, particularly in public universities. This study investigates the role of national culture on email usage among non-academic staff in Malaysian public universities using Hofstede’s National Culture mediated by the Technology Acceptance Model (TAM). Data was collected by using survey questionnaires among 217 non-academic staff in four public universities in Malaysia. The study found a significant positive relationship between long-term orientation (LT) and indulgence (I) with perceived ease of use (PEOU) while a significant negative relationship between power distance (PD) with perceived ease of use (PEOU). This study also found that the relationship between collectivism (C) and uncertainty avoidance (UA) with perceived usefulness (PU) on email usage is negative. Finally, both PEOU and PU have a significant positive relationship with email usage and PEOU has a significant positive relationship with PU on email usage. In conclusion, Malaysian public universities perceive that emails become more useful when they are easy to be utilised and that individual long-term orientation and indulgence of work affect this thought.